De facto powers and disruptive technologies: towards a surveillance democracy based on the dominance of digital platforms - Saura García, Carlos (Revista del CLAD Reforma y Democracia, 2023)
The purchase of Twitter (currently X) by Elon Musk for an amount of 44 billion dollars became one of the most important economic operations of the year 2022. This purchase has once again highlighted the problems that the instrumentalization of digital platforms by centers of power, de facto powers, or billionaires could pose for public opinion and for the proper functioning of the democratic system. This article studies various aspects related to the effects of digital platforms on modern societies such as addiction to them, their monopolization, the use of instruments of manipulation of public opinion or the creation of a context of mass social surveillance. The aim of this article is to expose the problems that can be caused by the instrumentalization of digital platforms and technologies for the proper functioning of public opinion and democracy.
Keywords: Digital Platforms; Attention Economy; Monopolization; Mass Surveillance; Political Manipulation; Surveilled Democracy